Hydrogen Bonding Selectivity in Molecular Assembly: A Novel 2:1 Molecular Complex of Caffeine and 4-Hydroxybenzoic Acid via C– H···O/O– H···O/O– H···N Hydrogen Bond Coupling - KUMAR MAHAPATRA, AJIT; SAHOO, PRITHIDIPA; FUN, H.K.; GOSWAMI, SHYAMAPROSAD (Asian Journal of Chemistry, 2010)
Caffeine (1) and 4-hydroxybenzoic acid (2) form a novel 2:1 molecular complex via C—H---O hydrogen bonding. Selectivity in the formation of hydrogen bonds in the X-ray structure of the complex is predicted by the relative acidity and basicity of the participating atoms in the groups. This is first time reported that caffeine is complexed with an aromatic hydroxy acid through two C—H---O hydrogen bonds involving N-CH3 hydrogen and ring hydrogen of caffeine.